Perceived effect of a training activity for medical students in community organizations - Gottin, Thomas; Foley, Veronique; Petit, Geneviève; Valois, Carol; Loignon, Christine (Canadian Medical Education Journal, 2024)
Background: Community service-learning activities (CSL) have been integrated into medical schools for several years. However, little data exists to understand the impact of this type of activity on students and communities. The purpose of this research was to explore the effect of a mandatory community-based training activity offered to medical students. Methods: A descriptive qualitative study was conducted with students and their host community organizations. Semi-structured interviews were conducted with 1st and 2nd year medical students who participated in CSL activities (pre n = 21, post n = 7). These interviews were conducted before and after the CSL activities. In addition, focused focus groups with leaders of community organizations (n = 17) involved in student training completed the study. Results: Experiences in a variety of socio-economic and cultural settings contributed to students' understanding of the concept of social vulnerability. CSL also generated a better understanding of the importance of community organizations in helping these vulnerable individuals. Conclusion: In the context of CSL, a better understanding of the individual and community organization factors that contribute to the development of competencies related to practice in a context of vulnerability is necessary to allow for a significant and often transformative experience for future physicians.